NAVIGATION ALGORITHM FOR OPTIMAL CHOICE OF THE CITY VEHICLE ROUTE - Ніколюк, Петро (SWorldJournal, 2025)
The study is a fundamentally new approach to solving an extremely important nowadays problem – the problem of congestion in any large city. The navigation task of the vehicle time-optimal routes choice has been solved. The research is based on the use of